2022
DOI: 10.1002/smr.2516
|View full text |Cite
|
Sign up to set email alerts
|

The Pandora's box of social, process, and people debts in software engineering

Abstract: In software engineering, technical debt (TD) has been widely investigated, but debt regarding social issues, people, and processes has not been explored as much. It should be noted here that we use nontechnical debt (NTD) as an umbrella term to cover social, process, and people debts. Although the number of studies on NTD in software is increasing, the majority of them are descriptive rather than rigorous, and there is no systematic development of cumulative knowledge. As a result, identifying the fundamental … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 34 publications
0
15
0
1
Order By: Relevance
“…En [24] se aborda la deuda no técnica (NTD) en ingeniería de software, un tema que no ha recibido la misma atención que la deuda técnica cuando se trata de deudas relacionadas con aspectos sociales, procesos y personas. El análisis comparativo entre las investigaciones sobre la deuda no técnica (NTD) en ingeniería de software y el presente estudio ofrece valiosas perspectivas sobre la importancia de la colaboración y la gestión efectiva de los aspectos sociales, procesos y personas en entornos de desarrollo de software.…”
Section: Discussionunclassified
“…En [24] se aborda la deuda no técnica (NTD) en ingeniería de software, un tema que no ha recibido la misma atención que la deuda técnica cuando se trata de deudas relacionadas con aspectos sociales, procesos y personas. El análisis comparativo entre las investigaciones sobre la deuda no técnica (NTD) en ingeniería de software y el presente estudio ofrece valiosas perspectivas sobre la importancia de la colaboración y la gestión efectiva de los aspectos sociales, procesos y personas en entornos de desarrollo de software.…”
Section: Discussionunclassified
“…Testing strategies such as integration, regression and user acceptance testing are significant challenges for case companies. Such test challenges lead to "test debt" [3]. Second, the teams encountered sprint-related challenges, which Ahmad and Tomas categorised as non-technical debt [3].…”
Section: Discussionmentioning
confidence: 99%
“…Larger companies typically have fewer interactions with their customers than smaller ones, making the customer unsatisfied at the time of delivery [21]. Kalenda et al [17] [3] highlighted that resistance to change and integration with non-agile business processes are critical challenges in agile scaling.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, the debt metaphor has also been used in requirements engineering [11]. Ahmad and Gustavsson [1] recently conducted a systematic mapping review on nontechnical debt in software engineering and found 17 studies that investigate social, process, and people debts. They reported that both [8,17] found lack of communication, collaboration and coordination to be the cause of social debt.…”
Section: Introductionmentioning
confidence: 99%